Productos turísticos y oferta turística del cantón Chambo, provincia de Chimborazo. - Gavilanes Molina, Marcela Catalina (2023)
The aim of this project is to establish the relationship between the products and the tourist offer of Chambo canton, Chimborazo province. The research methodology is applied with a quantitative, qualitative and field approach where the basic instrument of the research is a survey according to the independent variable "Tourism products" was applied to 245 tourists visiting the canton Chambo and the study dimensions were evaluated: tourist attractions, commercialization and travel; for the dependent variable "Tourist offer" was applied to 22 service providers, focusing on aspects such as tourist services, quality of destination and infrastructure, through the analysis of information it was evidenced that of the total tourists surveyed 41.63% state that they want to consume adventure tourism products; this allowed us to evaluate and corroborate how tourism products impact on the tourist offer of the canton Chambo. By checking hypotheses it was demonstrated that there is no relationship between tourist products and the tourist offer of the canton Chambo, because no new tourist products have been evidenced. Despite this, a situational diagnosis was made that showed the weaknesses in the tourist offer, and as a consequence a proposal was presented in which strategies were designed as an alternative to strengthen the tourist offer in the canton Chambo.